A Conversation with Regent Frances Wills: Humanizing Policymaking in Tumultuous Times. Issue 4 (2nd October 2022) - Clayton, Christine D.
ABSTRACT: This commentary retells a conversation with New York State Regent Frances Wills about policymaking in ways that value the human enterprise of teaching. The conversation addresses the first two years of Regent Wills' appointment to the state policymaking body which happens to coincide with the pandemic and significant shifts in New York's educational policies. Topics discussed include widening the lens in policymaking, lessons from the pandemic, teacher recruitment, rethinking the edTPA, and humanizing the profession. The conversation is edited according to the traditions of portraiture to value the aesthetic of Regent Wills' speech while presenting actual words from the taped transcript. While located in the particular context of New York State from 2020–2022, the conversation addresses national concerns such as the challenging task of recruiting and retaining a diverse community of dedicated teachers who can transform the profession.